A new species of the Aphaenogaster cecconii group (Hymenoptera: Formicidae) from Rhodes - Salata, Sebastian; Borowiec, Lech (Zootaxa, 2016)
Aphaenogaster charesi, a new species in the A. cecconii group, is described from two localities on the island of Rhodes. The recent revision of the group by Borowiec and Salata is updated with (1) a modified key to include this new species, (2) new locality and habitat data for A. jolantae Borowiec & Salata, 2014, and (3) corrected measurements for A. olympica Borowiec & Salata, 2014.